Khách hàng đồng tạo sinh dịch vụ y tế: Nghiên cứu trường hợp bệnh nhân tự sử dụng thiết bị y tế tại nhà - Nguyễn Huỳnh , Hương; Lê Nguyễn, Hậu (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
Nowadays, patients with chronic diseases are increasing rapidly. Most of them are outpatients. However, the rate of their adherence to physician recommendations is notably low. Based on the Service-dominant theory, this study explores the structural impacts of external and internal factors on diabetes participation in healthcare services. The analysis of data collected from 283 diabetes shows the impact of frontline staff (physician) support and social support (relatives) on patients’ blood glucose self-monitoring levels through co-creation capability and motivation. The results also show the relative importance and the direct/indirect influence of the mentioned factors in this specific context. Theoretical and practical implications are then discussed.